Collaboration between Government and Palm Oil Industry to Achieve Sustainability Development Goals in Indonesia - Handoko Limaho; Rudy Pramono; Rio Christiawan (Jurnal Mulawarman Law Review, 2022)
Palm oil plantation businesses have always been the subject of heavy scrutiny and are accused of causing the most environmental and social mishaps in Indonesia. Such condemnation comes from within the country and outside as well. Even though the palm oil industry is one of Indonesia’s biggest GDP contributors, the opposition in the past decade outweighs the support, and many attempts at reasoning fall on deaf ears. This article will argue that the need for transformation of the industry in order to support the nations’ sustainability development goals is an effort that involves all constituents. The relationship that is built upon the palm oil companies and its stakeholders must be met with certain legalities and support from the government in order to foster a green growth relationship that will sustain the economy and the environment, which will ultimately support Indonesia’s sustainable development goals.